Lumbar Posterior Transpedicular Screw Fixation and Fusion Applications; What We Do Peroperatively with 117 Spinal Instability Cases - Mustafa Güdük; Güray Bulut; Murat Hamit Aytar (Genel Tıp Dergisi)
Objective: In this study, we aimed to share our surgical principles and surgical outcomes in cases of fixation and fusion with lumbar posterior transpedicular screw-rod systems in our clinic. Methods: 117 patients who underwent posterolateral fusion surgery with lumbar posterior transpedicular screw-rod system between 2014 and 2017 were evaluated retrospectively. Dynamic lumbar radiographs, computed tomography and magnetic resonance imaging were performed in all cases before the operation. All patients were operated with microsurgical principles and internal fixation and posterolateral fusion were performed with posterior interpedicular screw-rod systems. Stabilization systems were evaluated with lumbar X-ray and/or computed tomography on the first postoperative day. In the 1st and 3rd months, lumbar X-rays were repeated. Results: All these patients, in whom lumbar spinal instability was detected clinically and radiologically, had low back and/or leg pain and different levels of neurological deficits. Of the cases, 23 were male and 94 were female. The mean age was 53.4 years. According to the Meyerding classification, there were grade I and II spondylolisthesis in 69, and 8 cases respectively, spinal stenosis in 28 cases, burst fracture in 1 case, compression fracture in 3 cases, disc herniation in 11 cases. The mean follow-up period was 28.6 months. Conclusions: Meticulous case selection, careful preoperative planning and adherence to spinal microsurgery principles will increase the success rate in lumbar posterior internal fixation and posterolateral fusion surgeries.